A comparison of radial keyhole strategies for high spatial and temporal resolution 4D contrast-enhanced MRI in small animal tumor models - Subashi, Ergys (American Association of Physicists in Medicine, 2013)
Purpose: Dynamic contrast-enhanced (DCE) MRI has been widely used as a quantitative imaging method for monitoring tumor response to therapy. The simultaneous challenges of increasing temporal and spatial resolution in a setting where the signal from the much smaller voxel is weaker have made this MR technique difficult to implement in small-animal imaging. Existing protocols employed in preclinical DCE-MRI acquire a limited number of slices resulting in potentially lost information in the third dimension. This study describes and compares a family of four-dimensional (3D spatial + time), projection acquisition, radial keyhole-sampling strategies that support high spatial and temporal resolution. Methods: The 4D method is based on a RF-spoiled, steady-state, gradient-recalled sequence with minimal echo time. An interleaved 3D radial trajectory with a quasi-uniform distribution of points in k-space was used for sampling temporally resolved datasets. These volumes were reconstructed with three different k-space filters encompassing a range of possible radial keyhole strategies. The effect of k-space filtering on spatial and temporal resolution was studied in a 5 mM CuSO(4) phantom consisting of a meshgrid with 350-μm spacing and in 12 tumors from three cell lines (HT-29, LoVo, MX-1) and a primary mouse sarcoma model (three tumors/group). The time-to-peak signal intensity was used to assess the effect of the reconstruction filters on temporal resolution. As a measure of heterogeneity in the third dimension, the authors analyzed the spatial distribution of the rate of transport (K(trans)) of the contrast agent across the endothelium barrier for several different types of tumors. Results: Four-dimensional radial keyhole imaging does not degrade the system spatial resolution. Phantom studies indicate there is a maximum 40% decrease in signal-to-noise ratio as compared to a fully sampled dataset. T1 measurements obtained with the interleaved radial technique do not differ significantly from those made with a conventional Cartesian spin-echo sequence. A bin-by-bin comparison of the distribution of the time-to-peak parameter shows that 4D radial keyhole reconstruction does not cause significant temporal blurring when a temporal resolution of 9.9 s is used for the subsamples of the keyhole data. In vivo studies reveal substantial tumor heterogeneity in the third spatial dimension that may be missed with lower resolution imaging protocols. Conclusions: Volumetric keyhole imaging with projection acquisition provides a means to increase spatiotemporal resolution and coverage over that provided by existing 2D Cartesian protocols. Furthermore, there is no difference in temporal resolution between the higher spatial resolution keyhole reconstruction and the undersampled projection data. The technique allows one to measure complex heterogeneity of kinetic parameters with isotropic, microscopic spatial resolution.